Metodos de conservacion in vitro del germoplasma - Roca, W.; Arias, D.I.; Chavez, R. (International Center for Tropical Agriculture, 1991)
In vitro conservation strategies are reviewed, with special reference to in vitro active and basic gene banks; likewise, important aspects that should be considered for in vitro conservation, such as regeneration, viability, genetic stability, and information systematization, are discussed. The 2 basic systems of in vitro germplasm conservation are detailed, namely growth limitation up to min. rates and total suppression of growth. The 1st system controls the growth rate through factors such as temp., nutrient and growth regulator concn., and osmotic concn.; in the 2nd system, this rate is reduced through low temp. (levels below - 150 degrees C). In the case of cassava, germplasm is maintained through meristem culture, using a combination of cryogenic techniques and min. growth storage conditions. The different stages of a collobarative project of an in vitro active gene bank between CIAT and the International Board for Plant Genetic Resources are indicated; this project provides standards for the adoption of in vitro cassava conservation by national institutions in tropical areas or for extrapolating these standards to other crops propagated vegetatively. (CIAT)